Murder, she spoke: the female voice's ethics of evocation and spatialisation in the true crime podcast. Issue 2 (3rd July 2017) - Greer, Amanda
Abstract: The female voice in cinema has been discussed throughout film sound theory as persistently de - acousmatised, denied the power of narrative creation and relegated to onscreen, visual space. This paper will contrast this visual containment of female vocalisations with that of the female-hosted podcast, in which nothing is or can be seen. The podcast offers alternative routes of resistance for the female acousmetre, allowing her to maintain her disembodied status. This is poignantly evident in the popular true crime podcast, My Favorite Murder, in which the acousmatic female hosts counter crime film and television's reliance on images of violated female bodies with purely aural recountings. Through their anti-ocularcentric reliance on the aurally evocative, rather than the visually manifested, these female voices transform themselves and the victims of their discussions into haunting spectres that force listeners to imaginatively reconstruct scenes of female-directed violence, while acknowledging the ethics of their complicity in the propagation and popularisation of these narratives. Thus, the true crime podcast is one potential site of doubled resistance against the de-acousmatisation of female voices and the visualisation of mutilated female bodies; this resistance leads to an ethics of the spectral, a Derridean mourning without end.